Exploring the Use of Collaborative Writing on Padlet in Teaching Narrative Writing - Sulfatun Hasanah; Ina Daril Hanna; Rini Listyowati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Narrative writing requires active skills and appropriate teaching strategies to help students organize ideas and express their creativity. This study aims to explore the implementation of collaborative narrative writing through the digital platform Padlet across two classroom meeting. The objective of this research is to describe the stages of collaborative writing using Padlet and identify the outcomes of its application. This qualitative study was conducted with eleventh-grade students at MA Misbahus Sudur Taman Baru, data collected through observations, interviews, and documentation. The findings indicate that during the first meeting, students required more guidance in using Padlet and understanding narrative text structure. However, by the second meeting, students showed improvement in independence and confidence. They became more active in collaborating within groups, providing feedback via Padlet's comment features, and revising their drafts based on feedback from peers and teachers. Despite encountering technical difficulties and initial confusion, both students and teachers demonstrated positive engagement. This study confirms that Padlet is effective in supporting students' narrative writing through structured yet flexible digital collaboration.